Bidirectional Transcription and the Regulation of Phage λ Repressor Synthesis - Spiegelman, Willard G. (1972)
There are two promoters for transcription of gene cI in phage λ, the gene that codes for phage repressor. The promoters, called pre and prm, are located on the distal (pre) and proximal (prm) sides of gene cro, which itself is adjacent to cI. Since cI and cro are transcribed in opposite directions, cI transcription initiating at pre gives rise to an antisense transcript of cro, while cI transcription initiating at prm does not. Pre, active after infection of a sensitive cell, is stimulated by products of phage genes cII and cIII, and may be located at the site defined by the mutant cY. Prm is active in an established lysogen. These conclusions are based on measurements of the rates of synthesis of antisense cro RNA, cI RNA, and repressor protein in infected and lysogenic cells. To measure antisense RNA, an assay based on the formation of nuclease-resistant, double-stranded RNA, specific to the cro region, was developed. These results raise the possibility that bidirectional transcription of cro has a regulatory function in phage λ.